Somatic incompatibility and genetic structure of fungal crops in sympatric Atta colombica and Acromyrmex echinatior leaf-cutting ants - Kooij, Pepijn W. (Elsevier, 2015)
Obligate mutualistic symbioses rely on mechanisms that secure host-symbiont commitments to maximize host benefits and prevent symbiont cheating. Previous studies showed that somatic incompatibilities correlate with neutral-marker-based genetic distances between fungal symbionts of Panamanian Acromyrmex leaf-cutting ants, but the extent to which this relationship applies more generally remained unclear. Here we showed that genetic distances accurately predicted somatic incompatibility for Acromyrmex echinatior symbionts irrespective of whether neutral microsatellites or AFLP markers were used, but that such correlations were weaker or absent in sympatric Atta colombica colonies. Further analysis showed that the symbiont clades maintained by A. echinatior and A. colombica were likely to represent separate gene pools, so that neutral markers were unlikely to be similarly correlated with incompatibility loci that have experienced different selection regimes. We suggest that evolutionarily derived claustral colony founding by Atta queens may have removed selection for strong incompatibility in Atta fungi, as this condition makes the likelihood of symbiont swaps much lower than in Acromyrmex, where incipient nests stay open because queens have to forage until the first workers emerge.